Bioethanol production in vacuum membrane distillation bioreactor by permeate fractional condensation and mechanical vapor compression with polytetrafluoroethylene (PTFE) membrane. (November 2018) - Li, Jianfeng; Zhou, Wencan; Fan, Senqing; Xiao, Zeyi; Liu, Yicai; Liu, Jingyun; Qiu, Boya; Wang, Yuyang
Graphical abstract: Highlights: High ethanol productivity and high accumulative production were achieved. High membrane flux with high PSI value was obtained. Reversible membrane fouling was observed for ethanol removal in situ from broth. Enhanced separation factor with permeate fractional condensation. Mechanical vapor compression made VMDBR being energy efficient. Abstract: A vacuum membrane distillation bioreactor (VMDBR) by permeate fractional condensation and mechanical vapor compression with PTFE membrane was developed for bioethanol production. Cell concentration of 11.5 g/L, glucose consumption rate of 5.2 g/L/h and ethanol productivity of 2.3 g/L/h could be obtained with fermentation continues lasting for 140 h. Membrane flux of over 10 kg/m 2 /h could be obtained for model solution separation. Higher temperature and flow rate could promote membrane separation. Membrane flux could be reduced to about 2000 g/m 2 /h with fermentation proceeding owing to the deposited cell on membrane surface. The membrane separation performance could be resumed by water rinse. High ethanol concentration of 421 g/L could be obtained by permeate fractional condensation with the process separation factor increased to 19.2. Energy of only 14 MJ/kg was required in VMDBR and the energy consumption would be reduced further if the compressed vapor could be used to heat the feed.